Unfair Wage Perceptions and Sleep: Evidence from German Survey Data - Christian Pfeifer (Institute for the Study of Labor (IZA), 2015)
The author uses large-scale German survey data for the years 2009, 2011 and 2013 in order to analyze the nexus between the individual perception of being unfairly paid and measures for quantity and quality of sleep, namely, hours of sleep during workweek and during weekend, happiness with sleep, and sleep disorders diagnosed by a doctor. Main findings of the regression analysis are that workers, who perceive their own wage as unfair, sleep significantly less during the workweek (1.2 to 2.5 percent), are significantly less satisfied with their sleep (1 to 5 percent) and are significantly more likely to have sleep disorders (7 to 36 percent). Moreover, workers with more weekly working hours sleep significantly less during the workweek (0.1 to 0.2 percent per hour) and are significantly less satisfied with their sleep (0.1 to 0.2 percent per hour). The size of the hourly wage is however not significantly correlated with any of the sleep outcomes and the household income seems also of minor importance, even though the estimated coefficients have the expected signs implied by substitution and income effects. The overall results suggest that unfair wage perceptions, which are related to stress, negatively affect workers' sleep and, consequently, their health.
Keywords: I12; J22; J31; 330; fairness; health; income; sleep quantity; sleep quality; wage; working hours